2013
DOI: 10.1177/1043659613481674
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perceptions of Patients Living With Hepatitis C in Karachi, Pakistan

Abstract: Patients with HCV experience profound challenges that are influenced by their level of education, financial capacity, cultural norms, family support, and the sensitivity of health care professionals. Several cultural practices existing in Pakistan identify the need for public awareness. The findings on health care professionals have implications for nursing and allied health continuing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…The behaviour of family members or friends has been reported to result in feelings of depression and isolation (23) and it was also reported previously by patients in Karachi, Pakistan, that they faced difficulties from their family member resulting in increased suffering (13). Breakup of relationships with spouses or fiancés were noted in this study and were also reported in a study from the United States (15).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The behaviour of family members or friends has been reported to result in feelings of depression and isolation (23) and it was also reported previously by patients in Karachi, Pakistan, that they faced difficulties from their family member resulting in increased suffering (13). Breakup of relationships with spouses or fiancés were noted in this study and were also reported in a study from the United States (15).…”
Section: Discussionsupporting
confidence: 59%
“…A recent study from Karachi reported that HCV patients had to face a number of problems which varied according to patients' education, income, societal and family background as well as the behaviour of health-care providers (13). However, few data are available that describe the experiences and stigma associated with both different types of hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies were conducted in Australia [2123, 25, 30, 32, 33, 38, 39, 51, 53, 56–59, 64, 65], fifteen in the UK [24, 31, 34, 35, 37, 40, 46, 47, 49, 52, 55, 60, 61, 63, 66], eight in the United States [26, 27, 36, 41, 43, 48, 54, 62], four in Canada [28, 29, 45, 50], and one each from Pakistan [42] and France [44]. The studies were published between 1999 [39] and 2014 [40, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Study participants reported a variety of physical symptoms, such as fatigue [27, 30, 3336, 40, 42, 46, 54, 62, 64, 66], weakness [27, 35], nausea [27, 30, 34, 64], pain [27, 34, 36, 42, 64, 66], swelling [27], headaches [30, 64], and sweating [30]. In addition, a number of studies reported participants experiencing psychological symptoms such as depression [27, 30, 66], anxiety or panic attacks [35], and irritability [36, 62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation